High-resolution record of temporal change in organic matter burial over the past ∼8,600 years on the northwestern continental slope of the South China Sea - Tong, Gang; Chen, Lilei; Zhang, Guangxu; Liu, Jian; Chen, Bin; Xu, Gang; Liu, Ming; An, Yuhui; Chen, Duanxin (Frontiers in Earth Science, 2023)
Sedimentary organic matter (SOM) on continental slopes in marine regions can sensitively record climatic and environmental changes. In this study, total organic carbon content (TOC), total nitrogen content (TN), and their stable isotope compositions (δ 13 C and δ 15 N) for sediments of core G02 were investigated (at ~24.2year resolution) to reveal the temporal variations in organic matter sources and the main controls on the sources and distribution of buried organic matter on the northwestern continental slope of the South China Sea over the last ~8600 yr. Results of a δ 13 C binary mixing model reveal that ~82.3% ± 3% of SOM is derived from marine autochthonous sources. We suggest that the carbon and nitrogen contents and compositions of SOM are governed by distinct factors. The more positive δ 15 N values before the Pulleniatina Minimum Event occurrence are ascribed to stronger subsurface water intrusion by the Kuroshio Current, which led to enhanced subsurface denitrification and in turn counteracted the effect of mixing with surface water caused by the East Asian winter monsoon. Sedimentary δ 13 C values show a fluctuant decrease during ca. 8.6-3.0 cal kyr BP and a conspicuous increase during ca. 3.0-1.4 cal kyr BP. These changes are attributed to the decrease of marine productivity induced by the continuous weakening East Asian monsoon effect and the decrease of terrigenous organic carbon input induced by the weakened Indian summer monsoon precipitation, respectively. Since ca.1.4 cal kyr BP, human activities have become the dominant factor in controlling the production and distribution of organic carbon. The results provide an important basis for understanding of source-sink processes of organic matter and the factors influencing these processes on continental slopes in low-latitude marginal seas.